طريقة كروماتوغرافيا سائلة عالية الأداء مؤشرة للثبات لمقايسة بنتوكسيفيلين في أشكاله الصيدلية - عبود, آيات (Latakia University Journal -Medical Sciences Series, 2017)
تصف هذه الدراسة طريقة كروماتوغرافيا سائلة عالية الأداء مؤشرة للثبات لمقايسة بنتوكسيفيلين في أشكاله الصيدليه. جرى فصل المادة الدوائية بنجاح عن نواتج التدرك، بعد تعريضها لشروط اجهاد، باستعمال عمود C18 وطور متحرك مكون من ماء وميثانول (60: 40، حجم: حجم بتدفق 1 مل/د وطول موجة 272 نانومتر. كان زمن احتباس بنتوكسيفيلين نحو 14 دقيقة. جرى توثيق مصدوقية الطريقة فيما يتعلق بالخطية، الدقة، المضبوطية، والانتقائية. أثبتت الخطية على مجال من 0.6 مكغ/مل الى 3.5 مكغ/مل وكان R2 0.994. كانت الطريقة مضبوطة (قيم استعادة 100.1%) ودقيقة (RSD > 2%). كان حد الكشف وحد الكم 0.2 مكغ/مل و0.4 مكغ/مل على التوالي. طبقت الطريقة بنجاح لمقايسة بنتوكسيفيلين في المضغوطات مديدة التحرر المتوفرة في السوق السورية. The present study describes a simple stability-indicating reversed-phase HPLC assay for pentoxifylline in its pharmaceutical dosage forms. Separation of the drug and the degradation products، under stress conditions was successfully achieved on a C18 column utilizing water: MeOH (60:40 v/v)، pumped at a flow rate of 1 ml min-1 with UV detection at 272 nm. The retention time of pentoxifylline was about 14 min. The method was satisfactorily validated with respect to linearity، precision، accuracy and selectivity. The response was linear in the range of 0.6-3.5 μg/ml with R2 0.994. The method was accurate (recovery 100.1%) and precise (RSD < 2%). Detection and quantification limit were 0.2 μg/ml and 0.4 μg/ml respectively. The suggested method was successfully applied for the analysis of pentoxifylline in extended release tablets available in Syrian market.